Étudier les infrastructures pour ouvrir les boîtes noires politiques. Entretien avec Timothy Mitchell - Timothy Mitchell; Pierre Charbonnier; Julien Vincent (Tracés, 2018)
This interview with leading historian and political scientist Timothy Mitchell, by Julien Vincent (historian) and Pierre Charbonnier (philosopher) introduces to a work where the relationship between politics and infrastructures is central. Mitchell first describes the intellectual context in which he developed his conceptual framework, incorporating both postcolonial studies and Science and Technology Studies. He then discusses his work in relation to concepts of modernity, State, technology, and fossil fuels. The interview finally addresses the political implications of his work, particularly after the election of Donald Trump as US president.